2018
DOI: 10.1016/j.fuel.2018.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Controlled releases of asphaltene inhibitors by nanoemulsions

Abstract: Asphaltene precipitation is usually responsible for many flow assurance problems such as wettability changes and pore clogging in reservoirs, fouling in wellbore tubings and production surface facilities. This study develops a novel approach by using nanoemulsions (NE) for controlled delivery and release of asphaltene inhibitors (AI) to minimize asphaltene precipitation with reduced AI amount. LUMiSizer was utilised to study the effectiveness and performance of controlled release by three cases on asphaltene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…The total chemicals usage (% R TC ) are again lower than 4 vol% DBSA by a factor of 10%. These results in very good agreement with the previous work 27 for reducing AI amount and the total chemicals used, which found that 4 vol% DBSA and 20 vol% of DBSA NEs gave the same values of the instability indexes and the sedimentation rates.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The total chemicals usage (% R TC ) are again lower than 4 vol% DBSA by a factor of 10%. These results in very good agreement with the previous work 27 for reducing AI amount and the total chemicals used, which found that 4 vol% DBSA and 20 vol% of DBSA NEs gave the same values of the instability indexes and the sedimentation rates.…”
Section: Resultssupporting
confidence: 91%
“…Such a synergistic effect may overcome the hydrogen bond forces of water molecules and enhance the bounded molecules at the interface, resulting in more hydrophobicity of the oil phase. The procedure of synthesis of nanoemulsions with the presence and absence of AI was elaborated in the previous study, 27 as depicted in the schematic diagram in Fig. S1 in the ESI.…”
Section: Methods and Measurementsmentioning
confidence: 99%
See 3 more Smart Citations